Protection of the Rights, Freedoms and Interests of Ukrainian Citizens in Court Proceedings During the War - Kyrychenko, Yurii; Kurakin, Oleksandr; Kyrychenko, Viktor; Nazarenko, Pavlo; Baieva, Liliia (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The article aims to reveal access to justice during wartime in cases related to protecting citizens' rights, freedoms and interests. Active hostilities are taking place in most regions of Ukraine, making it impossible to deliver justice in administrative courts. However, the High Council of Justice has resolved this issue properly, so access to justice in Ukraine during wartime in cases related to protecting citizens' rights, freedoms and interests is currently possible following the Constitution of Ukraine. Courts are obliged to administer justice even under martial law, and their powers are not suspended. To ensure access to the Court, the Supreme Court changed the territorial jurisdiction of about one hundred courts in Ukraine. In connection with the introduction of martial law in Ukraine, all procedural terms shall be renewed, consideration of cases shall not be stopped, and excessive formalism on the part of judges shall not allowed. The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, and methods of analysis and synthesis. The article analyzes the Decision of the ECtHR, and based on this, the author concludes that the ECtHR considers financial costs as an obstacle to accessing justice. Access to Court is adequate only when a person will have a real opportunity to challenge wrongful actions in practice. According to the ECtHR, the construction of Article 6 of the Convention is effective only if the case is considered in Court. The ECtHR singles out the right to access the Court as a component of the right to a fair trial. Attention is drawn to the fact that courts must take all measures to restore violated rights.